(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
The objective of this paper is the study of the life cycle inventory (LCI) for underground mining of small, clustered deposits of Dinaric Alps-type bauxites, mined in the mountains near Jajce, a town in Bosnia and Herzegovina, in the period 2010-2020. Modelling of the life cycle inventory was done based on the company’s internal reports and project documentation for a variant of the sublevel caving method that is using drilling and blasting. Four mines, located on three exploitation fields, were found in different phases of mine life, different levels of tectonic disturbances and different types of energy: diesel, electricity, compressed air. The main results of this study are the inventory of underground bauxite exploitation made based on long-term data, the life cycle of one bauxite deposit, and the emission factors from blasting. Underground mining in this case proved to be energy intensive: An average of 52-92 MJ/t was required (as opposed to 37 MJ/t for surface bauxite exploitation in Italy). At the same time, underground bauxite exploitation caused only 5.6-6.4% of the transformation of natural land that is above mines and deposits. The operations relying on diesel fuel caused local emissions in air and underground. The operation relying on electricity for DC locomotive and generation of the compressed air were without local emission into the air, although energy efficiency was probably reduced using compressed air as mechanical energy. At the state level, impacts depend on the country’s energy mix, which is still quite dependent on fossil fuels. Engineering estimates of blasting emissions indicated detonators and ammonium nitrate explosives as a potentially important source of environmental impacts. The mining industry would benefit significantly from cleaner energy in electricity generation (energy sector) in Bosnia and Herzegovina. The path of air emissions in the underground system, especially lead and nitrogen compounds, needs to be further explored.